2017
DOI: 10.1021/acs.jctc.6b01106
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Test of the OPLS-AA Force Field for Calculating Free Energies of Mixing and Comparison with PAC-MAC

Abstract: We have calculated the excess free energy of mixing of 1053 binary mixtures with the OPLS-AA force field using two different methods: thermodynamic integration (TI) of molecular dynamics simulations and the Pair Configuration to Molecular Activity Coefficient (PAC-MAC) method. PAC-MAC is a force field based quasi-chemical method for predicting miscibility properties of various binary mixtures. The TI calculations yield a root mean squared error (RMSE) compared to experimental data of 0.132 kBT (0.37 kJ/mol). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…The OPLS-AA force field has previously been used to model mixture of alkane-alcohol, alkane-amine and alcohol-amine with satisfactory results for various thermodynamic properties. 47 Bulk liquid simulations have also been performed in this work to ensure that the OPLS-AA force field represents well the miscibility of ethanol and iso-octane at various temperatures in the range of 270-390 K. We observed that the OPLS-AA force field parameterization used in this work reproduces the bulk experimental density of an equimolar mixture of iso-octane and ethanol (less than 2% deviation), 48 as well as the full miscibility of both components. All LJ interactions have a cutoff of 10Å and electrostatic interactions are handled using the PPPM method.…”
Section: Simulation Methodsmentioning
confidence: 86%
“…The OPLS-AA force field has previously been used to model mixture of alkane-alcohol, alkane-amine and alcohol-amine with satisfactory results for various thermodynamic properties. 47 Bulk liquid simulations have also been performed in this work to ensure that the OPLS-AA force field represents well the miscibility of ethanol and iso-octane at various temperatures in the range of 270-390 K. We observed that the OPLS-AA force field parameterization used in this work reproduces the bulk experimental density of an equimolar mixture of iso-octane and ethanol (less than 2% deviation), 48 as well as the full miscibility of both components. All LJ interactions have a cutoff of 10Å and electrostatic interactions are handled using the PPPM method.…”
Section: Simulation Methodsmentioning
confidence: 86%
“…Some force fields have been parametrized based on experimental data on binary mixtures, such as vapor-liquid equilibria (e.g., TraPPE), 65 while established force fields have been tested for their performance in reproducing such equilibria 66 or other related thermodynamic properties of mixtures (e.g., the free energy of mixing). 67 We performed mixing assays to estimate whether two Martini solvent models mixed or not, and compared the observed behavior to reference experimental data. Data regarding the most common solvents are commonly available as solvent miscibility tables.…”
Section: Solvent Mixtures: Martini Miscibility Tablementioning
confidence: 99%
“…Every structure was neutralized at the physiological pH and a library of 36,229 potential ligands was created including the stereoisomers and tautomers (Srivastava, Pal & Misra, 2018). Target protein structures files were prepared using Schrödinger Protein Preparation Wizard by removing excess waters and were minimized using OPLS 2005 force field (Clark et al, 2019;Sweere & Fraaije, 2017).…”
Section: Virtual Screening Against Npassmentioning
confidence: 99%